DECOLONIZING IDENTITY AND SURVIVAL THROUGH CULTURAL HYBRIDITY: POST-COLONIAL ANALYSIS OF JOHNSON’S YELLOW WIFE - Syed Musharaf Hussain Shah; Yasir Abbas; Quratulain Ijaz; Dr. Sajid Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This study delves into the complexities of decolonization of identity and cultural hybridity in a post-colonial context as depicted in Johnson’s Yellow Wife (2021) using Fanon’s theoretical framework from The Wretched of the Earth (1963). It also touches upon the themes of cultural hybridity and identity formation aligning with Bhabha’s theory on cultural hybridity and in-between spaces within cultures from The Location of Culture (1994). It aims at how characters and societies grapple with post-colonial identity complexities, addressing unequal power structures, and negotiating the influences of various cultures. The theoretical frameworks provided by Fanon (1963) and Bhabha(1994) contribute valuable insights to comprehend these dynamics at a deeper level. The method involves meticulous analysis of selected textual excerpts to reveal the intricate relationships between individual and group identities and the exercise of power within societies that have experienced colonization. The analysis underscores how enslaved individuals, exemplified by Pheby, navigate the intricate dynamics of slavery by strategically balancing their availability to white slave owners while maintaining invisibility, revealing the complex negotiation of agency and dignity within the colonial system. In the context of hybridity, it reveals characters’ conflicting emotions when faced with kindness from those in authority, highlighting the nuanced challenges inherent in racial discrimination and power imbalances within the enslaved community. This exploration contributes to a broader narrative on racial oppression, emphasizing enduring spirits in colonial systems, enriching discussions on freeing identity from the clutches of colonial power and blending two cultures in historical contexts.